A new diarylheptanoid from the rhizomes of Zingiber mekongense - Arthittaya Chareonkla (2018)
A new diarylheptanoid, (3S,5S)-3,5-diacetoxy-1,7-bis(3,4,5- trimethoxyphenyl)heptane (1), together with the known docosyl trans-ferulate (2), (1S,2S,4S)-p-menthan-1,2,4-triol (3), 5αH-eudesmane-4α,11-diol (4), 5αH-eudesmane-4β,11-diol (5), 4α,10β-dihydroxy- 1βH,5αH-guaia-6-ene (guaianediol) (6), (+)-galanolactone (7), (E)-labda-8(17),12(13)-dien-15,16-olide (8), labda-8(17),13(14)-dien-15,16-olide (9), 3,5-dihydroxy-7,4′-dimethoxyflavone (10) and 3,5,3′- trihydroxy-7,4′-dimethoxyflavone (11) were isolated from the rhizomes of Zingiber mekongense. Their structures were determined by spectroscopic methods. The stereochemistry of 1 was proved through chemical conversion. Compounds 1, 4-7 and 9-11 exhibited anti-HIV-1 activities in the anti-syncytium assay using δTat/rev MC99 virus and 1A2 cell line system, while only compounds 7 and 11 were found active in the HIV-1 reverse transcriptase assay. © 2011 Elsevier B.V. All rights reserved.